1998
DOI: 10.1101/gr.8.8.809
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence of a 93.4-kb Contig from Chromosome 3 of Trypanosoma cruzi Containing a Strand-Switch Region

Abstract: We have initiated large-scale sequencing of the third smallest chromosome of the CL Brener strain of Trypanosoma cruzi and we report here the complete sequence of a contig consisting of three cosmids. This contig covers 93.4 kb and has been found to contain 20-30 novel genes and several repeat elements, including a novel chromosome 3-specific 400-bp repeat sequence. The intergenic sequences were found to be rich in di-and trinucleotide repeats of varying lengths and also contained several known T. cruzi repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…These GSS (Genomic Sequence Survey) sequences represent 4.3 Mb of readable sequences or ∼10% of the parasite haploid genome, which is ∼40 Mb (Frohme et al 1998). The total GC content of the sequence produced was 50.9%, a value that is slightly larger than the one obtained from estimations made on 8796 T. cruzi ESTs (49.6 %), and the one obtained for 93.4 Kb from chromosome 3 (48.5%) (Andersson et al 1998). The fractional GC content for all the GSSs varied from 0.18-0.71, with ∼69% of the sequences falling in the 0.47-0.57 range.…”
Section: Overall Structure Of the T Cruzi Genomementioning
confidence: 65%
See 1 more Smart Citation
“…These GSS (Genomic Sequence Survey) sequences represent 4.3 Mb of readable sequences or ∼10% of the parasite haploid genome, which is ∼40 Mb (Frohme et al 1998). The total GC content of the sequence produced was 50.9%, a value that is slightly larger than the one obtained from estimations made on 8796 T. cruzi ESTs (49.6 %), and the one obtained for 93.4 Kb from chromosome 3 (48.5%) (Andersson et al 1998). The fractional GC content for all the GSSs varied from 0.18-0.71, with ∼69% of the sequences falling in the 0.47-0.57 range.…”
Section: Overall Structure Of the T Cruzi Genomementioning
confidence: 65%
“…Recently, the complete sequence of chromosome 1 from L. major Friedlin (Myler et al 1999) and a partial sequence of chromosome 3 from T. cruzi (Andersson et al 1998) were obtained, showing in both cases a similar organization with two clusters of genes per chromosome transcribed in opposite directions. These studies also showed that the gene density is high in the regions where genes are clustered, with ∼1 gene every 3.6 Kb in both cases.…”
mentioning
confidence: 99%
“…Recently, Andersson et al (1998) reported the complete sequence of a 93.4 kb contig from T. cruzi chromosome 3. This contig contains a strand-switch region where genes appear to be organized in two long clusters harboring multiple genes on the same strand, with the two clusters oriented in opposite directions.…”
Section: Genome Research 1273mentioning
confidence: 99%
“…cruzi can be estimated to have ∼12,000 genes from the gene density of about 1 gene per 3.5-4 kb, as revealed by genomic sequencing (Andersson et al 1998) and the haploid genome size of ∼45 Mb in the T. cruzi reference clone CL Brener (J. Swindle, unpubl.). Because a considerable part of the T. cruzi genome comprises several large gene families as well as other repeat sequences (Requena et al 1996), this number of genes should be an overestimate.…”
Section: Identification Of Genes Present In Kinetoplastidsmentioning
confidence: 99%
“…Neither vaccines nor safe and efficient drug treatment are presently available against this debilitating disease. The genome project for T. cruzi involves both genomic sequencing (Andersson et al 1998) and identification of functional genes through generation of expressed sequence tags (ESTs) (Brandão et al 1997;Verdun et al 1998), a cost-effective technique in gene discovery (Venter 1993;Okubo and Matsubara 1997). The ongoing parasite genome projects of the three kinetoplastids, Leishmania major (Blackwell 1997), Trypanosoma brucei (Melville 1997), and T. cruzi (Zingales et al 1997), are critical in identifying orthologous genes involved in mechanisms among kinetoplastids.…”
mentioning
confidence: 99%